State control over private military and security companies in armed conflict - Tonkin, Hannah, 1981- (Cambridge studies in international and comparative law., 2011)
"The past two decades have witnessed the rapid growth and consolidation of the global private security industry. Tens of thousands of contractors working for private military and security companies (PMSCs) now provide a wide range of services to states, international organisations, corporations and non-governmental organisations around the world. Many PMSCs operate in zones of armed conflict, where they carry out functions that were formerly the exclusive domain of the armed forces. In this context, PMSCs have performed coercive activities such as offensive combat, armed security and the detention and interrogation of prisoners, as well as non-coercive activities such as military advice and training, transport, housing and intelligence collection and analysis"--